Categorical Features of Aspectuality in English and Uzbek Languages - Hasanovna , Davlatova Muhayyo (Miasto Przyszłości, 2024)
In the course of our research, we paid special attention to the category of aspectuality, and first of all, we tried to determine whether there is a morphological category of verb types in the English and Uzbek languages. In the research of the meaning of the verb color, it is possible to achieve the intended goal only by referring not only to grammatically formed categorical units, but also to all linguistic means that express aspectuality. That is why specific theories and approaches of aspectuality have arisen based on the structure of a certain language.